The Kinerja PMI Kabupaten Klaten Dalam Upaya Penanggulangan dan Pencegahan Penyebaran Virus Covid - 19 di Kabupaten Klaten: Kinerja, PMI, Covid - 19 - Endang Lestari (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The objectives of the study were to determine and analyze: (1) the performance ofPMI in Klaten Regency in efforts to control and prevent the transmission of theCovid-19 virus in Klaten Regency; (2) Obstacles faced by PMI Klaten Regency inefforts to control and prevent the transmission of the Covid-19 virus in KlatenRegency; (3) Solutions taken to anticipate the obstacles faced by PMI KlatenRegency in efforts to overcome and prevent the transmission of the Covid-19 virusin Klaten Regency.This research is a qualitative descriptive with a case studyapproach. Data collection techniques using observation, interviews, anddocumentation. Data validation used triangulation of data sources and methods.The data analysis technique used was descriptive qualitative analysis. The resultsof the study concluded that: (1) PMI Klaten Regency's performance in efforts toovercome and prevent the transmission of the Covid-19 virus in Klaten Regency,namely: very high responsibility in achieving target targets, quite effectiveactivities, quite productive in realizing work programs, and quality of servicepretty good; (2) Obstacles faced by PMI Klaten Regency in efforts to control andprevent the transmission of the Covid-19 virus in Klaten Regency, namely: lack ofpublic awareness about healthy and clean lifestyles and concern for theenvironment, and lack of human resources, due to the reach of the Klaten Regencyarea which is infected by the Covid-19 pandemic is quite widespread, and evenlydistributed in almost every District, while PMI Klaten employees and volunteersare also limited in number; (3) The solutions taken to anticipate the obstaclesfaced by PMI Klaten Regency in efforts to overcome and prevent the transmissionof the Covid-19 virus in Klaten Regency, namely: increasing socialization andeducation to the community by taking into account the characteristics ofcommunity members, increasing human resource capacity in the field ofprevention and control. Covid-19 prevention.Keywords: Performance, PMI, Covid-19